Lesinurad in combination with allopurinol: a randomised, double-blind, placebo-controlled study in patients with gout with inadequate response to standard of care (the multinational CLEAR 2 study). Issue 5 (7th November 2016) - Bardin, Thomas; Keenan, Robert T; Khanna, Puja P; Kopicko, Jeff; Fung, Maple; Bhakta, Nihar; Adler, Scott; Storgard, Chris; Baumgartner, Scott; So, Alexander
Abstract : Objectives: Determine the efficacy and safety of daily lesinurad (200 or 400 mg orally) added to allopurinol in patients with serum uric acid (sUA) above target in a 12-month, randomised, phase III trial. Methods: Patients on allopurinol ≥300 mg (≥200 mg in moderate renal impairment) had sUA level of ≥6.5 mg/dL (≥387 µmol/L) at screening and two or more gout flares in the prior year. Primary end point was the proportion of patients achieving sUA level of <6.0 mg/dL (<357 µmol/L) (month 6). Key secondary end points were mean gout flare rate requiring treatment (months 7 through 12) and proportions of patients with complete resolution of one or more target tophi (month 12). Safety assessments included adverse events and laboratory data. Results: Patients (n=610) were predominantly male, with mean (±SD) age 51.2±10.90 years, gout duration 11.5±9.26 years and baseline sUA of 6.9±1.2 mg/dL (410±71 µmol/L). Lesinurad at 200 and 400 mg doses, added to allopurinol, significantly increased proportions of patients achieving sUA target versus allopurinol-alone therapy by month 6 (55.4%, 66.5% and 23.3%, respectively, p<0.0001 both lesinurad+allopurinol groups). In key secondary end points, there were no statistically significant treatment-group differences favouring lesinurad. Lesinurad was generally well tolerated; the 200 mg dose had a safety profile comparable with allopurinol-alone therapy. Renal-related adverse events occurred in 5.9% of lesinurad 200 mg+allopurinol, 15.0% of lesinurad 400 mg+allopurinol and 4.9% of allopurinol-alone groups, with serum creatinine elevation of ≥1.5× baseline in 5.9%, 15.0% and 3.4%, respectively. Serious treatment-emergent adverse events occurred in 4.4% of lesinurad 200 mg+allopurinol, in 9.5% of lesinurad 400 mg+allopurinol and in 3.9% of allopurinol-alone groups, respectively. Conclusion: Lesinurad added to allopurinol demonstrated superior sUA lowering versus allopurinol-alone therapy and lesinurad 200 mg was generally well tolerated in patients with gout warranting additional therapy. Trial registration number: NCT01493531 .